A companion to the Latin language - Clackson, James (Blackwell companions to the ancient world., 2011)
A Companion to the Latin Language presents a collection of original essays from international scholars that track the development and use of the Latin language from its origins to its modern day usage. Brings together contributions from internationally renowned classicists, linguists and Latin language specialistsOffers, in a single volume, a detailed account of different literary registers of the Latin languageExplores the social and political contexts of LatinIncludes new accounts of the Latin language in light of modern linguistic theorySupplemented with illustrations covering the developme.